The Influence Of Customer Experience, Perceived Ease Of Use, Perceived Usefulness, Perceived Risk On Behavioral Intention To Use Mobile Banking In Malaysia - Suyono Saputra; Selli Selli; Wisnu Yuwono (UNIVED Press, 2025)
This study tries to investigate how customer experience factors, perceived ease of use, perceived usefulness, perceived risk can influence the behavioral intention to use mobile banking through attitude as a mediating variable. This research model was examined within the context of Batam City residents who have used mobile banking in Malaysia involving 258 respondents. Sampling was carried out using purposive sampling technique and PLS-SEM analysis with SmartPLS 3.0 software to analyze the data. The research results show that customer experience, perceived ease of use, perceived usefulness and perceived risk are proven to be able to influence the attitude towards behavioral intention of the Batam City residents who have used mobile banking in Malaysia.